Case Report: A long-term survival case of primary malignant melanoma of the lung with meningeal metastasis - Wu, Ying; Wei, Yanchun; Meng, Xiang; Zhou, Yufu (Frontiers in Oncology, 2025)
BackgroundMalignant melanoma originating in the lungs is relatively rare, accounting for only 0.01% of lung tumors, and has a poor prognosis and is prone to distant metastasis. Notably, melanoma is the third most common source of intracranial metastases in adults, after lung and breast cancer. Primary malignant melanoma of the lung with meningeal metastasis is more rare and has a worse prognosis. There is no effective and unified treatment plan in clinical practice, and the main treatment is comprehensive treatment, which mainly includes surgery, radiation therapy, immunotherapy and targeted therapy.Case presentationThe patient was a 52-year-old male with no history of smoking. PET-CT showed a mass in the main bronchus of the right lung, consistent with the metabolic changes of malignant melanoma. Combined with pathology, we finally identified the patient as a primary pulmonary malignant melanoma. About two years later, the patient developed meningeal metastases. The patients was mainly treated with radiation therapy combined with immunotherapy, and the overall survival was about 30 months.ConclusionsThe diagnosis of pulmonary primary malignant melanoma requires a combination of many factors and is easy to be misdiagnosed. At present, there is no specific effective treatment plan, and such patients have a poor prognosis, are prone to distant metastasis, and their survival will be greatly shortened. The survival period of the patient in this case is longer than the average survival period of such patients, and the possibility of benefiting from immunotherapy is higher. Radiotherapy also reduces the discomfort symptoms of the patient to a certain extent, prolongs the survival of the patient, and provides certain ideas for clinical treatment.